Noninvasive detection of skeletal muscle underperfusion with near-infrared spectroscopy in patients with heart failure - Wilson, J R; Mancini, D M; McCully, K; Ferraro, N; Lanoce, V; Chance, B (Circulation (New York, N.Y.), 1989)
The present study was undertaken to determine whether near-infrared spectroscopy can be used to noninvasively assess skeletal muscle oxygenation in patients with heart failure. The difference between light absorption at 760 and 800 nm was used to assess hemoglobin-myoglobin oxygenation. Initial studies conducted in isolated canine gracilis muscle demonstrated that 760-800-nm absorption correlated closely (r = -0.97 +/- 0.01) with venous hemoglobin O2 saturation when the muscle was stimulated to contract at 0.25-5.0 Hz. In normal subjects (n = 6) and patients with heart failure (n = 8), 760-800-nm absorption changes from the vastus lateralis muscle were monitored at rest, during progressive maximal bicycle exercise, and during thigh cuff inflation to suprasystolic pressure, an intervention designed to assess minimal hemoglobin-myoglobin oxygenation. Absorption changes were expressed relative to the full physiologic range noted from rest to thigh cuff inflation. During exercise, normal subjects exhibited an initial increase in hemoglobin-myoglobin oxygenation followed by a progressive decrease in oxygenation to 27 +/- 13% of the physiologic range at the peak exercise workload of 140 +/- 9 W. In contrast, patients exhibited an initial decrease in hemoglobin-myoglobin oxygenation with the first workload, followed by a progressive further decrease to 26 +/- 13% of the physiologic range at a peak exercise workload of 60 +/- 8 W, less than half the peak workload noted in the normal subjects. At all exercise loads, hemoglobin-myoglobin oxygenation was significantly less in the patients than in the normal subjects. These data suggest that near-infrared spectroscopy can detect impaired skeletal muscle O2 delivery in patients with heart failure. This technique could provide a valuable method of assessing muscle O2 delivery in patients, particularly before and after therapeutic interventions.